Coma Simulation Enhances Learning of Brainstem Reflexes - Diana Barratt (Association of American Medical Colleges, 2014)
Abstract Introduction This 90-minute simulation provides participants with hands-on experience practicing the coma examination in a safe environment. It requires only a low-fidelity mannequin (or a simple life-sized doll), with eyelids that can be opened and a head that can be turned. No technical support is needed, and the simulation can be run in any room large enough to accommodate a six-foot table or hospital bed and the participants. Methods During the introduction, participants discuss the cranial nerves responsible for brainstem reflexes. When the simulation begins, participants play the role of treating physicians. They must demonstrate the ability to take a focused history from a family member, perform a brain death examination, review the medical record (including vital signs and ventilator logs, a CT scan, and laboratory evaluation), counsel the family member, and manage conflict. After the debriefing process, all participants type a brief summary of the case, email it to the faculty, and discuss it with the group. While the optimal size of the group is four to six participants, the simulation can be run effectively with larger groups. Results During the 2011-2012 academic year, 30 students each submitted one history and physical on an actual coma patient. Students without exposure to the simulation documented an average of 57% of the items, whereas students with exposure to the simulation documented an average of 70% of the items. Discussion Implementation of the coma simulation improved medical student documentation in actual coma patients, compared to historical controls. Over the last 2 years, approximately 80 third-year medical students have participated in this coma simulation.